Genetic Mechanism of Ozone-induced Reductions in Grain Yield and Quality of Rice - Sawada, Hiroko (Journal of Japan Society for Atmospheric Environment / Taiki Kankyo Gakkaishi, 2020)
The tropospheric ozone concentrations have rapidly increased in the developing Asian countries. Elevated ozone concentrations reduce the yield of crops, including rice, which is the most important food crop in Asia. Previous studies have indicated that the current level of ozone is sufficiently high enough to reduce the grain yield of rice. However, the molecular mechanisms response to chronic ozone stress on the growth and the yield are poorly understood. The author and collaborators have carried out the experiments of chronic ozone exposure using several dozen domestic and foreign rice cultivars, the proteome analysis in leaves of rice cultivars, which show the different ozone sensitivities, and the genotypic analysis of quantitative trait loci. As a result, we found a novel mechanism of ozone-induced yield reduction in rice, especially indica cultivars, which is not caused by the reduction in photosynthetic activity as associated with visible leaf injury and leaf senescence. In this paper, the results of our studies on the molecular mechanism of ozone-induced reduction in grain yield and quality of rice are described.